2014
DOI: 10.1038/srep07546
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223-3p targeting SEPT6 promotes the biological behavior of prostate cancer

Abstract: MicroRNAs (miRNAs) present frequently altered expression in urologic cancers including prostate, bladder, and kidney cancer. The altered expression of miR-223 has been reported in cancers and other diseases in recent researches. MiR-223 is up-regulated in systemic lupus erythematosus and rheumatoid arthritis. In neoplastic diseases, miR-223 is proved to be up-expressed in plasma or serum and cancer tissues compared with normal tissues in pancreatic cancer, gastric cancer, et al. However, whether altered expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 49 publications
3
66
2
Order By: Relevance
“…In particular, ZEB1 was proven to be suppressed by miR-223–3p in BC cell lines treated with Ginkgolide B 36. Furthermore, SEPT6 was reported to be specifically targeted by miR-223-3p in prostate cancer cell lines 37. Among miRNAs involved in inflammation, miR-17-5p deserves particular attention as member of miR-17/92 cluster involved in tumorigenesis, immune diseases, cardiovascular diseases, neurodegenerative diseases and aging 14.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ZEB1 was proven to be suppressed by miR-223–3p in BC cell lines treated with Ginkgolide B 36. Furthermore, SEPT6 was reported to be specifically targeted by miR-223-3p in prostate cancer cell lines 37. Among miRNAs involved in inflammation, miR-17-5p deserves particular attention as member of miR-17/92 cluster involved in tumorigenesis, immune diseases, cardiovascular diseases, neurodegenerative diseases and aging 14.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al (2011) [24] shown that miR-223 was able to stimulate non-metastatic gastric cancer cells to invade by targeting a tumor suppressor gene named EPB41L3 . Wei et al (2014) [31] also found accelerated invasive ability of Prostate Cancer cell lines when miR-223-3p were artificially added to the cells, but in this case through SEPT6 targeting.…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers found that overexpression of miR-223 was positively correlated with tumor recurrence and metastasis in patients with colorectal cancer [33], hepatocellular cancer [34] and non-small cell lung cancer [35]. Several in vitro studies also verified that miRNA-223 promoted lung cancer, ovarian cancer and prostate cancer cells invasion via targeting EPB41L3 [36] , SOX11 [37] and SEPT6 [38] respectively. These inconsistent results may be due to the different roles of the target genes of miRNA-223 in the tumor.…”
Section: Discussionmentioning
confidence: 99%